SCORM based learning management system for online training - Garg, Anubha (Kansas State University, 2012)
The Biosecurity Research Institute (BRI) facility at Kansas State University is a huge biocontainment facility to conduct research on infectious diseases that pose a threat to plant, animal and human health. The BRI Training and Education Program is currently offline; i.e., classroom sessions are taken to provide this training and education. The objective behind taking up this project was to move the entire training and education module of Biosecurity Research Institute online, instead of having a classroom session for each training course, with an subject matter expert (SME) to come and take the training session. The aim is to develop an online training system which is synchronized with the information in the BRI Research Project Database. The employees will only have to login to the website, scroll through the list of courses they are enrolled in, take the courses, write the assignments/quizzes assigned to the course and then submit the quizzes. They can also self-enroll themselves into courses, if they are given the permission to do so. The SME’s of the courses can create new courses, upload the course materials, enroll users into the courses, and assign deadlines to course completion. Once the student submits the course quiz or assignments, the SME’s can grade the quiz, assign a final grade to the students, and give feedback on their performance. They can even reassign the course in case of poor performance by the student. The administrators of the website can assign roles to different personnel, give permissions according to need and requirement, add/delete courses, and change the appearance of the website. The project is to be done using a Learning Management System called Moodle. Moodle (Modular Object Oriented Dynamic Learning Environment) is an online learning management system designed to allow interaction between teachers and students. The back-end database used is SQL Server 2008 R2 and additional tools used are Adobe Presenter (with Microsoft Power Point 2010) to create the courses in SCORM format.
Keywords: Moodle learning management system; Online training; Shareable content object reference model; Computer Science (0984)